Lithium Cluster Segregation in Coherent Contraction Twin Boundaries of Magnesium Alloys - Ge, Bingcheng; Yang, Meng; Zu, Qun; Guo, Jianxin; Tian, Yongjun; Peng, Qiuming (Acta materialia, 2020)
Modification of twin boundaries has been deemed as a potential strategy to achieve high strength in combination with good ductility for many engineering alloys. Herein, we report a unique Li cluster segregation phenomenon in coherent contraction twin boundaries of Mg alloys. The structures at the atomic scale have been investigated by transmission electron microscopy. Meanwhile, the driving force for segregation and strengthening mechanisms have been elucidated by first-principles calculations and molecular dynamics simulations, respectively. Experimental results show that the segregated Li cluster with a hexagonal close-packed structure is coherent with a contraction twin. Subsequently, theoretical calculations reveal that the Li cluster is prone to occupy the interface vacancy in the contraction twin boundaries, following which it grows along the twin boundaries preferentially. Finally, both dynamics simulations and experimental observations demonstrate that the formation of Li cluster in contraction twin boundaries can not only directly pin dislocation movement analogous to precipitation strengthening, but also improve the critical shear strain of contraction twin boundaries, inhibiting their deformation or widening. The finding of cluster segregation in twin boundaries also occurs in other systems, which might open an avenue for twin boundary engineering to tune the mechanical properties of metals and ceramics. We firstly report a unique lithium luster segregation phenomenon in coherent contraction twin boundaries of Mg alloys by high-resolution TEM observations, DFT calculations and MD simulations. The finding might provide some implications for twin boundary engineering to tune the mechanical properties of metals and ceramics. [Display omitted]